Pengaruh Metode Kreatif Inovatif Brilian Aktif Religius (KIBAR) terhadap Baca Tulis Al Qur’an Siswa Kelas V SD Muhammadiyah I Bontang - Dzulficar, Safriadly; Ihsan, Muh (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to determine the effect of the Creative, Innovative, Brilliant, Active, Religious (KIBAR) method on improving the reading and writing skills of the Qur'an of grade V students of SD Muhammadiyah 1 Bontang in the 2024/2025 Academic Year. The background of this study is the low reading and writing skills of some students, so a learning method is needed that can improve their motivation and skills as a whole. This study uses a quantitative approach with a survey method. The subjects of this study were all 47 grade V students of SD Muhammadiyah 1 Bontang, so this study is a population study. Data collection techniques were carried out by conducting closed questionnaire observation interviews and documentation to explore students' perceptions and learning outcomes related to the application of the KIBAR method which has been tested using validity and reliability tests to ensure that the instruments used are feasible and consistent in measuring research variables. Data analysis was carried out using descriptive and inferential statistics. Descriptive statistics are used to describe general data trends, while inferential statistics use the T test and F test with the help of the SPSS program. The results of the analysis showed a significance value of 0.004 in the T test and F test, which means that there is a significant influence of the KIBAR method on improving students' reading and writing of the Qur'an, because the significance value is less than 0.05.